Introduction to Python for science and engineering - Pine, David J. (Boca Raton, FL : CRC Press, 2019)
Series in Computational PhysicsSteven A. Gottlieb and Rubin H. Landau, Series Editors Introduction to Python for Science and Engineering This guide offers a quick and incisive introduction to Python programming for anyone. The author has carefully developed a concise approach to using Python in any discipline of science and engineering, with plenty of examples, practical hints, and insider tips. Readers will see why Python is such a widely appealing program, and learn the basics of syntax, data structures, input and output, plotting, conditionals and loops, user-defined functions, curve fitting, numerical routines, animation, and visualization. The author teaches by example and assumes no programming background for the reader. David J. Pine is the Silver Professor and Professor of Physics at New York University, and Chair of the Department of Chemical and Biomolecular Engineering at the NYU Tandon School of Engineering. He is an elected fellow of the American Physical Society and American Association for the Advancement of Science (AAAS), and is a Guggenheim Fellow.
6.2.3 Setting plotting limits and excluding data6.2.4 Subplots; 6.3 Logarithmic Plots; 6.3.1 Semi-log plots; 6.3.2 Log-log plots; 6.4 More Advanced Graphical Output; 6.4.1 An alternative syntax for a grid of plots; 6.5 Plots with multiple axes; 6.6 Mathematics and Greek symbols; 6.7 The Structure of matplotlib: OOP and All That; 6.7.1 The backend layer; 6.7.2 The artist layer; 6.7.3 The PyPlot (scripting) layer; 6.8 Contour and Vector Field Plots; 6.8.1 Making a 2D grid of points; 6.8.2 Contour plots; 6.8.3 Streamline plots; 6.9 Three-Dimensional Plots; 6.10 Exercises; 7 Functions
OCLC-licensed vendor bibliographic record.
Keywords: Python (Computer program language); Computer programming; Engineering -- Data processing; Science -- Data processing; COMPUTERS / Programming Languages / Python; COMPUTERS / Programming Languages / General; MATHEMATICS / General; SCIENCE / Physics